بناء موديل رقمي لحل معادلات المياه قليلة العمق (معادلات Saint-Venant) باستخدام طريقة العناصر المنتهية - محمد, نسرين; صالح, ايهاب مالك (Latakia University Journal -Engineering Sciences Series, 2016)
باعتبار أن معادلات الجريان تخضع لعلاقات تفاضلية بمشتقات جزئية، فإن حل هذه المعادلات ليس بالأمر السهل باستخدام الطرق الرياضية المعروفة وقد يكون مستحيلاً في بعض الحالات بسبب طبيعة الشكل الهندسي الذي يتم الجريان حوله (مثل بدن السفينة) وتعقيد الشروط الحدية بالإضافة إلى وجود حدود غير مستقرة تبين تبعية النظام الفيزيائي المدروس لمتحول الزمن. لذلك يتم اللجوء حديثاً إلى الطرق الرقمية لحل هذا النوع من المعادلات مثل: طريقة العناصر المنتهية وطريقة التفاضلات المنتهية وطريقة الحجوم المنتهية وطريقة عناصر الحدود (BEM). ومع ذلك فإن استخدام هذه الطرق يتطلب معايير ضبط استقرارية الجملة من حيث التقريب الرقمي للحد غير المستقر وتحقق القانون الفيزيائي الذي يضبط الجملة وهنا يكمن محور هذا البحث. Since the flow equations are governed by differential relations with partial derivatives, the solution of these equations is not easy by using known mathematical methods and it maybe impossible in some cases because of the nature of the geometric shape that the is flowing around (such as the hull of ship) and the complexity of the boundary conditions in addition to the existence of the unstable terms related to the unsteady physical system. So now they resort to the newly numerical methods, such as Finite Elements Method, Finite Differences Method, Finite Volumes Method and Boundary Elements Method (BEM) to solve this kind of equations. However, the use of these methods requires standards of controlling the stability of the system in the function of the numerical approximation of the unstable term as well as the verification of the physical law that controls the system and here lies the focus of this research